The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1086/306880
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Nonthermal Plasma Motions of Coronal Loops in a Solar Active Region

Abstract: We present a spectroscopic observation of a solar active region NOAA 7590 with a coronagraph at the Norikura Solar Observatory, which provides high-resolution spectra of the visible coronal emission lines (Fe X j6374, Fe XIV j5303, Ca XV j5694) with a spatial sampling of Nonthermal veloci-2A .0 ] 2A .3. ties (m) estimated from Fe X j6374, Fe XIV j5303, and Ca XV j5694 in this observation are 14È20, 10È18, and 16È26 km s~1, respectively. The Ðrst two results are consistent with the results obtained by Cheng et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 28 publications
4
30
2
Order By: Relevance
“…The value of VNTH averaged over the image is about 27 km s −1 , nearly independent of resolution. This is somewhat higher than the nonthermal velocity of 17.6 ± 5.3 km s −1 measured with EIS (Brooks & Warren 2016), the most-probable velocity of 15 km s −1 observed with IRIS (Testa et al 2016), and the values of 14 -26 km s −1 observed at the Norikura Solar Observatory (Hara & Ichimoto 1999). Therefore, the transverse waves in our model have relatively high velocities that are only marginally consistent with the available spectroscopic observations.…”
Section: Effect Of the Waves On Spectral Line Profilessupporting
confidence: 57%
See 1 more Smart Citation
“…The value of VNTH averaged over the image is about 27 km s −1 , nearly independent of resolution. This is somewhat higher than the nonthermal velocity of 17.6 ± 5.3 km s −1 measured with EIS (Brooks & Warren 2016), the most-probable velocity of 15 km s −1 observed with IRIS (Testa et al 2016), and the values of 14 -26 km s −1 observed at the Norikura Solar Observatory (Hara & Ichimoto 1999). Therefore, the transverse waves in our model have relatively high velocities that are only marginally consistent with the available spectroscopic observations.…”
Section: Effect Of the Waves On Spectral Line Profilessupporting
confidence: 57%
“…We predict that the Alfvén waves should be detectable as variations in Doppler shift, provided the instrument has sufficiently high spatial resolution (FWHM < 0.5"). The rms value of the non-thermal velocity is predicted to be nearly independent of spatial resolution, and is about 27 km s −1 , which is high compared to the observed values (Brooks & Warren 2016;Testa et al 2016;Hara & Ichimoto 1999). Therefore, despite not providing enough heating, the AWT model is already injecting as much energy into the corona as is consistent with spectroscopic observations.…”
Section: Discussionmentioning
confidence: 64%
“…More often it is defined as an Alfvén flux, v 2 v A (Priest 1982;Foukal 1990;Saba & Strong 1991), for a wave propagating at the Alfvén speed with amplitude v. Variations in the definition of the Alfvén flux use the observed nonthermal speed (Hara & Ichimoto 1999) or the mean-square velocity toward the observer hv 2 k i (Erdélyi et al 1998) in the place of v. These Alfvén flux expressions differ from the one used in this work in two respects. They do not include the second term in equation (14) for the flux of the longitudinal mode, and they assume that the propagation occurs at the Alfvén speed, instead of at the shock speed (v sh > v A ), as obtained in these simulations.…”
Section: Energy Fluxesmentioning
confidence: 95%
“…The majority of nonthermal velocities, derived from spectral line broadenings and attributed to random turbulence, flows, or unpolarized wave amplitudes, lie in the 1 6 ð ÞÂ10 4 m s À1 range (Feldman & Behring 1974;Saba & Strong 1991;Erdélyi et al 1998;Banerjee et al 1998;Hara & Ichimoto 1999;Ruderman 1999). Exceptionally larger values of about 1 Â 10 5 m s À1 are reported (Acton et al 1981;Withbroe et al 1985), although some reservations exist (Saba & Strong 1991;Hara & Ichimoto 1999). Observations that consider the anisotropy in the velocity distributions produce wave amplitudes on the order of 10 5 m s À1 perpendicular to the magnetic field in coronal holes (Kohl et al 1998;Leer & Marsch 1999).…”
Section: Unstratified Runsmentioning
confidence: 99%
“…We study Alfvén waves as they carry a large energy flux due to the high Alfvén velocity in the corona. Studies by Hara & Ichimoto (1999) and other authors strongly imply that Alfvén waves may be present in observational data of coronal loops and play a key role in coronal heating. We therefore simulate asymmetric plasma flow (Noci & Zuccarello 1983;Craig & McClymont 1986) with Alfvén wave dissipation acting as the driving force.…”
Section: Introductionmentioning
confidence: 89%